# How do you solve #n + (n + 1) = 32#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (n + (n + 1) = 32), you would first simplify by combining like terms:

(n + n + 1 = 32)

Then, combine the (n) terms:

(2n + 1 = 32)

Next, isolate the variable (n) by subtracting 1 from both sides:

(2n = 31)

Finally, divide both sides by 2 to solve for (n):

(n = 31/2 = 15.5)

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7